Analysis of Bioethanol Purification with Two Outlet Distillation System - Iqbal Zulfikar; Bambang Irawan (Asian Journal Science and Engineering, 2023)
The purpose of this study is to analyzes of the process of purifying bioethanol produced by a distillation apparatus that uses two holes of different heights. The equipment used in this study is a distillation prototype tool which has two steam holes coming out of the vessel, with different height positions. The research method used is experimental. Data collection was based on the results of distillation experiments with the independent variable alcohol content in the solution, the dependent variable alcohol content resulting from the distillation process and the control variable is steam temperature and processing time. The results of the study were processed with statistics showing that the position of the holes affects the product resulting from the alcohol content in bioethanol, a high hole position will produce bioethanol with a greater alcohol content. The alcohol content in the solution that is put into the distillation vessel affects the distillation results, the greater the alcohol content, the greater the alcohol product. The interaction between the position of the holes and the alcohol content in the solution affects the amount of alcohol product in the bioethanol. input solution containing low alcohol cannot reach the distillation results of bioethanol with high alcohol content. Bioethanol through the top hole has a higher alcohol content than that through the bottom hole. The alcohol content in the solution affects the difference in the alcohol content produced between the upper and lower holes. Distillation can produce bioethanol with a high alcohol content of up to 96%, with a solution containing about 85% alcohol. This distillation process can be done privately so that everyone can make fuel for their own vehicles. Keywords: Bioethanol Purification, Distillation System, Purifying Bioethanol